Diversity of planthoppers (Hemiptera: Fulgoromorpha) in rice associated with weeds in Argentina - Marino, Ana Maria (2014)
An assemblage of Fulgoromorpha in a rice agroecosystem from La Plata city was studied for thefirst time inArgentina, considering those species associated with rice and the surrounding weeds, their seasonality, sex ratiosand parasitoidism. Samples were obtained from 2006 to 2010 in a ricefield and in the surrounding weeds.Fourteen species from three families of Fulgoromorpha were associated with rice, most of them native species.The delphacidsChionomus haywardi, Toya propinquaandDelphacodes kuscheliwere the most abundant on rice.Population peaks occurred afterflooding of rice and before anthesis. The nativeC. haywardiwas more abundantin rice than in weeds, while the opposite was confirmed forT. propinqua, a well-known cosmopolitan grassspecialist. The difference of abundances ofD. kuscheliin rice and weeds was not significant. Our results highlightthe dominance ofC. haywardiduring all sampling years in the rice agroecosystem as well as the role ofsurrounding weeds as an alternative microhabitat for planthoppers instead of rice. The strepsipteranElenchustenuicorniswas the only recorded parasitoid and showed no preference for any of the insect hosts.